Fitopatogenos en los cultivos de pastos y forrajes en Cuba - Gonzalez Arias, G.=700 1 Lopez Mesa, M.O.; Amat Novo, Z.; Estrada Vilardel, G.; Lopez Manes, D.
(En, Es)
Ilus., 31 ref.
Keywords: ORGANISMOS PATOGENOS; PASTIZALES; CUBA; FITOPATOGENOS; PASTOS; FORRAJES